Invited letter to the editor on the editorials on “High dose irradiation after pleurectomy/decortication or biopsy for pleural mesothelioma treatment” - Parisi, Elisabetta; Romeo, Antonino (Journal of Thoracic Disease, 2018)
It is with great interest that we read the two editorials, “Non-ablative hypofractionated hemithoracic radiation—a new standard of care in mesothelioma?” by de Perrot and Cho (1) and “Lung-sparing intensity-modulated radiotherapy in malignant pleural mesothelioma: palliative or potentially radical?” by Botticella and De Ruysscher (2), both addressed to our previous publication on hypofractionation and pleural mesothelioma (3). We thank the physicians for their comments and take the opportunity of responding in this Letter to the Editor.